Development Pattern of Mitigation, Adaptation and Protection Strategies for the Food System of the Kampung Naga Indigenous Community in Facing Climate Change - Nuryaman, Hendar; Setiawan, Perdi; Mutiarasari, Nurul Risti; Djuliansah, Dedi; Suyudi, Suyudi; Setiawan, Iwan; Riyanto, Riko; Efendi, Anggi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Climate change has become a global challenge that directly impacts the food systems of indigenous communities, including Kampung Naga in Tasikmalaya Regency. However, studies and management of the impacts of extreme climate change on the food systems of indigenous communities indicate gaps, and are even neglected. Therefore, this research aims to formulate strategies for mitigation, adaptation, and protection of the food systems of the Kampung Naga indigenous community in facing climate change, using a case study method with Soft Systems Methodology analysis. The key informants in this study are representatives of the Kampung Naga community, neighborhood leaders, customary chiefs, youth representatives, household representatives, as well as representatives from Neglasari Village Government and Field Agricultural Extension Officers. Primary data from key informants were collected through surveys, in-depth interviews, observations, and focus group discussions (FGD) using guidelines, while secondary data were sourced from various literature. Through the SSM analysis stages, it was found that the transformation of the food system cannot be separated from social structures, cultural values, and living customary institutions. The analysis results indicate that an effective strategy must actively involve local actors, integrate traditional knowledge with scientific approaches, and consider the dimensions of efficacy, efficiency, and effectiveness in the transformation process. This study produced a conceptual model that is contextual and participatory, and can serve as a basis for developing food security policies based on local wisdom by implementing various improvement actions including strengthening human resources and actor regeneration, enhancing the self-sufficiency of local production inputs, developing products and post-harvest processes, strengthening synergy among actors, reinforcing institutions and networks, as well as community-based documentation and research. These findings are expected to contribute to building a resilient, fair, and sustainable food system. These findings are expected to contribute to building a resilient, just, and sustainable food system amid the threat of climate change.